Substitusi Jagung Menggunakan 3 Jenis Kulit Pisang yang Berbeda Dalam pakan Terhadap Histomorfologi Vili Usus Itik Hibrida - Bagus Andika Fitroh; Abdul Hakim; Adib Norma Respati (Agrotechnology Innovation (Agrinova), 2019)
This study was aimed to evaluate the utilization of banana peel meal as alternatives to substitution of corn in the diets based on the histomorphology of intestinal villi and visceral organ on hybrid ducks. A total of 105 male day old duck used in a completely randomized design (CRD) with 7 treatment was done through 3 replications, with each replication consisted of 5 Hybrid ducks. The treatment used is replacing corn wtith banana peel meal half of it (25%) and all of it (50%), PB= basal feed without banana peel meal; K25 and K50 = basal feed with kepok banana peel meal; T25 and T50 = basal feed with tanduk banana peel meal; R25 and R50 = basal feed with raja banana peel meal. If was significant differences were analyzed using orthogonal contrast. The paramater collected are high and width of villi and visceral organ on the Hybrid ducks. The results of the study showed that the utilization of 3 different types of banana peel meal on ducks have no significant effect on high and width of villi and visceral organ. It could be concluded that 3 different types of banana peel meal have no content or substances that can change high and width of villi and viceral organ on hybrid ducks.